Water Reclamation from Primary Municipal Wastewater Treatment Plant Effluent by Membrane Distillation - Nguyen, Quynh-Mai (Journal of Technical Education Science, 2023)
In this work, Direct Contact Membrane Distillation (DCMD) was applied for the treatment of municipal wastewater collected from the primary clarifier of a municipal wastewater treatment plant (MWWTP). The water flux at 60℃ and 20℃ for the feed and permeate side, respectively was 51 kg/m2h in treating the primary effluent. Meanwhile, the electrical conductivity of distillate was in the good range at 1.5 – 1.8 S/cm. Most of the representative parameters for water reuse (SS, nitrate, nitrite, phosphate, total coliform, and turbidity) in the primary effluent were completely removed in MD module operation with PTFE (polytetrafluoroethylene)/ PP (polypropylene) bi-composite membrane. However, limited rejection rate was observed only in ammonia removal due to the volatility of ammonia. Pretreatment of the primary MWWTP effluent by NaOCl showed only 15% decline in water flux for 28 hours of continuous operation. Periodic membrane cleaning with 3% HCl applied for non-pretreated feed recovered initial permeate flux up to 80 - 95% and yielded highly purified distillate in long-term operation of MD system.